Transparansi Pendataan Program Bantuan Sosial Tunai dalam Penanggulangan Kemiskinan di Lingkungan Bebidas Kelurahan Pegesangan Kota Mataram - Fardi, Muhammad; Inka Nusamuda Pratama; Darmansyah; Amil (Pencerah, 2023)
In general, the problem of poverty is a social problem that is always relevant to be studied continuously. This is not only because the problem of poverty has existed for a long time and is still present among us, but its symptoms are increasing along with the multidimensional crisis that is still being faced by the Indonesian people. the purpose of this study is whether the implementation of the Cash Social Assistance Program in the Bebidas Environment, Pagesangan Village, Mataram City has been running transparently. The research design is something that is very essential or important before conducting research. The approach in writing this scientific paper is a qualitative approach. The qualitative approach is used for the reason that it is easier to adapt when faced with different field realities because the qualitative approach is dynamic. Data collection techniques using observation techniques, interviews, documentation, while data analysis techniques through the stages of data collection, data reduction, data presentation, drawing conclusions. The openness of the process in the transparency of the distribution of BST in the Pegasangan sub-district is that transparency has been implemented properly because all information is known to the sub-district government, providing information through the media as well as outreach to the public.